2022
DOI: 10.1096/fj.202200943r
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell RNA sequencing for traumatic spinal cord injury

Abstract: Traumatic spinal cord injury (tSCI) is a severe injury of the central nervous system (CNS) with complicated pathological microenvironment that results in hemorrhage, inflammation, and scar formation. The microenvironment of the injured spinal cord comprises heterogeneous neurons, glial cells, inflammatory cells, and stroma-related cells. Increasing evidence has indicated that the altered cellular and molecular microenvironment following tSCI is a key factor impeding functional recovery. Single-cell RNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…Neurotrauma and stroke represent another group of CNS disorders triggering substantial cellular heterogeneity that has been investigated by single-cell transcriptomics (Wilhelmsson et al, 2017;Moulson et al, 2021;Cao et al, 2022). Shi et al (2021) reported varying phagocytic properties of astrocytes in mouse models of hemorrhagic and ischemic strokes.…”
Section: Neurotrauma and Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Neurotrauma and stroke represent another group of CNS disorders triggering substantial cellular heterogeneity that has been investigated by single-cell transcriptomics (Wilhelmsson et al, 2017;Moulson et al, 2021;Cao et al, 2022). Shi et al (2021) reported varying phagocytic properties of astrocytes in mouse models of hemorrhagic and ischemic strokes.…”
Section: Neurotrauma and Strokementioning
confidence: 99%
“…Neurotrauma and stroke represent another group of CNS disorders triggering substantial cellular heterogeneity that has been investigated by single-cell transcriptomics (Wilhelmsson et al, 2017 ; Moulson et al, 2021 ; Cao et al, 2022 ).…”
Section: Neurotrauma and Strokementioning
confidence: 99%
“…The subsequent stage is characterized by secondary injury, where the spinal cord tissue experiences disrupted local blood circulation. The production of reactive oxygen, nitric oxide, and free fatty acids is neurotoxic, inducing prolonged damage to the local neurons and axons [25,26]. Therefore, in the control group, the diminishing NF200 mRNA content is attributed to the ongoing death of local neurons due to secondary injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes mount context-specific responses to CNS injuries ( Yu et al, 2020 ). For example, profiling astrocyte transcriptomes by microarray or single-cell RNA sequencing (scRNA-Seq) in stab wound injury, lipopolysaccharide (LPS)-induced neuroinflammation, ischemic stroke, SCI, and neurodegeneration reveals disease-specific gene expression ( Zamanian et al, 2012 ; Liddelow et al, 2017 ; Cao et al, 2022 ). Liddlelow et al categorized transcriptionally distinct astrocyte subsets into “A1” and “A2,” with opposing effects in various disease states: A1 astrocytes are pro-inflammatory and neurotoxic, whereas A2 astrocytes promote tissue repair and are neuroprotective.…”
Section: Astrocytesmentioning
confidence: 99%